Implications of Organizational Culture and Work Discipline on The Performance of PT 'X' Employees - Wijayaningsih, Rini; Nur Azizah, Intan; Surjaatmadja, Surachman (International Journal of Advanced Multidisciplinary, 2023)
The researcher will conduct a study entitled "Implications of Organizational Culture and Work Discipline on Employee Performance at PT. 'X'. The population in this study were all employees of PT 'X', the number of samples used in the study followed the slovin formula, totaling 109 respondents. To obtain research results that are in accordance with the research objectives, the data analysis method uses multiple regression with two independent variables, namely Organizational Culture and Employee Discipline and one dependent variable, namely Employee Performance. The tools used are SPSS 24 for Windows. Based on research data that has been obtained from the results of an analysis regarding the influence of organizational culture and work discipline on employee performance at PT 'X' it is concluded the simultaneous test (f-test) this study concluded that together organizational culture and work discipline have implications for employee performance in a positive and significant way for employee performance at PT. 'X'.